2014
DOI: 10.1508/cytologia.79.331
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxic Effects and Reproductive Abnormalities Induced by e-Waste Contaminated Underground Water in Mice

Abstract: Summary Indiscriminate disposal of electronic wastes (e-wastes) in Nigeria is on the increase. The release of hazardous substances from these wastes may have harmful consequences on the environment and public health. This study was designed to investigate the potential in vivo genetic and reproductive toxicity of e-waste contaminated underground (well) waters obtained from Alaba International and Computer Village electronic markets in Lagos, Nigeria, using the murine micronucleus (MN), sperm morphology and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Comparing the upper values of Cd in water with the WHO guidelines, it can be seen that some concentrations are above the recommended limit (see Figure S7 ). These limit exceedances have been observed in China [ 46 , 51 , 70 , 75 ], Nigeria [ 11 , 74 ] and India [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the upper values of Cd in water with the WHO guidelines, it can be seen that some concentrations are above the recommended limit (see Figure S7 ). These limit exceedances have been observed in China [ 46 , 51 , 70 , 75 ], Nigeria [ 11 , 74 ] and India [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The upper bound median value was 0.01 mg/L ( Table 2 and Figure S9 ). The highest concentrations were recorded in China [ 46 ], followed by Nigeria [ 74 ], Thailand [ 54 ], India [ 56 ], Australia [ 71 ] and Ghana [ 68 ] (see Figure S9 ). It should be noted that according to the analysis of the upper values reported in the literature, water from around recycling sites [ 46 , 54 , 74 , 75 ] is more contaminated with Pb, followed by recycling sites [ 11 , 54 , 56 , 70 , 74 ] (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Significant increase in the number of morphologically abnormal sperm has been associated with infertility (Wyrobek et al 1984). Induction of abnormal sperms has been assumed to be due to an abnormal chromosome (Bruce et al 1974), minor alteration in testicular DNA (Giri et al 2002), point mutation (Narayana et al 2002, Alabi andBakare 2015) and mistakes in the spermatozoa-differentiating process during spermatogenesis (Odeigah et al 1997, Bakare et al 2005. The studies of Odeigah et al (1997) and Agunbiade et al (2012) reported that abnormalities in sperm heads might occur by physiological, cytotoxic or genetic mechanisms or alterations in testicular DNA, which in turn disrupts the process of differentiation of spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…16,39 Soil leachate and well water samples from the Alaba international and Computer village electronic markets in Lagos State, Nigeria showed both mutagenic and genotoxic properties in plant and animal models. 16,24,25,[40][41][42] Exposure of T. guineensis juveniles to varying concentrations of e-waste leachate could be genotoxic to fish. 39 Hazardous heavy metals such as As, Cd, Hg, Pb from e-waste are known to cause cancer.…”
Section: Health Effectsmentioning
confidence: 99%